Direct somatic embryogenesis and shoot organogenesis from leaf explants of Primulina tabacum - G. H. Ma; C. X. He; H. Ren; Q. M. Zhang; S. J. Li; X. H. Zhang; B. Eric (Biologia Plantarum, 2010)
An efficient propagation system via somatic embryogenesis and shoot organogenesis and plant regeneration system for endangered species Primulina tabacum Hance was established. Thidiazuron (TDZ) was the key plant growth regulator for inducing somatic embryogenesis and kinetin (KIN) and 6-benzylaminopurine (BAP) were the key cytokinins for inducing shoot organogenesis from leaf explants. TDZ combined with BAP or KIN in the induction Murashige and Skoog medium induced both somatic embryos and adventitious shoots. Leaf explants with abaxial site in contact with the medium induced less somatic embryos or adventitious shoots compared to inversely placed leaf explants and the optimum pH was 6.5-7.0. Secondary somatic embryos or adventitious shoot could be induced from primary somatic embryos using TDZ and BAP. Shoots developed adventitious roots on rooting medium containing 0.5 μM indole-3-butyric acid and 0.2 % activated carbon. Over 90 % of plantlets survived following acclimatization and transfer to potting mixture (sand:Vermiculite:limestone; 1:2:1).